Features Of Younger pupils’ Idea Of Rich And Poor People - Ianovska, Svitlana; Turenko, Rimma; Samokhin, Oleksiy; Ziarmand, Angella (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article deals with psychological characteristics of primary school children idea of a poor and rich man. It is shown that at early school age children defie the limits, signs of poverty and wealth, qualities of poor and rich, the nature of their relationships with others, their social signifiance. Perceptions of poor and rich images are related to both poor and rich fantasy characters, and with images of real people who are formed in the process of interaction with parents, peers and others.